Workshop untuk Meningkatkan Keahlian HCTS dalam Membuat Virtual Event - Wibowo, Andreas Christianto; Zahrandika, Muhammad Raffi; Jayawardhana, Irman (Prasetiya Mulya Publishing, 2022)
Primary data was gathered from a group of stakeholders through direct interview or online chat for those who are unavailable for such direct interviews. The objective of this research is to find the root problem that occurred during the 2020 HCTS as a virtual event held by Sun Eater, followed by a proposal of alternative solutions for said problems. The data collection is done with a qualitative research manner through the help of in-depth interviews with 2020 HCTS event personnels. The main problem was found to be “The lack of human resource skills in conducting an online event” by using the Severity and Urgency Matrix theory. The conceptual approach that was utilized during the construction of an alternative solution was the DMAIC, Event Management, and sub-domains knowledge of EMBOK theory.